Productivity of Laying Hens Second Phase with Free Feeding Choice - Auliya Chanifuddin Luthfi; Suhardi Suhardi; Eudia Christina Wulandari (Tropical Animal Science, 2020)
This study aim to determine the nutritional needs of laying hens according to physiological and environmental conditions in order to support the productivity of laying hens with free feeding choice. This research was conducted in Sidoharjo, Sumbung, Cepogo, Boyolali. Thirty layers of laying hens, age 52 weeks used in this study. The chicken were fed freely selectively with premix, corn, rice bran, and concentrate feed as measured ad libitum. Parameters measured were consumption, HDP, shell thickness and weight, albumen index, yolk index, and haugh index. The results were analyzed quantitatively by reading data with the graph. The results showed that the dietary intake of laying hens was lower than the standard, however, the nutrient needs could be fulfilled because the nutritional content of the feed ingredients was good. It’s can be seen from the high HDP, shell weight and thickness, also good egg index. Laying hens are able to fulfill their nutrient needs with the free feeding choice treatment.